INOVASI PENGEMBANGAN BAHAN AJAR PAI INTERAKTIF BERBASIS SCHOOLOGY UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 1 PEULIMBANG - Zulfannur (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
This research aims to develop interactive teaching materials for Islamic Education (PAI) using the Schoology platform to improve students’ learning motivation at SMA Negeri 1 Peulimbang. Using a qualitative descriptive approach, the study explores the design, implementation, and impact of Schoology-based learning. Data were gathered through interviews, classroom observations, and document analysis. Findings show that Schoology integration enhances motivation by providing engaging, flexible, and interactive experiences through videos, quizzes, and discussion forums. Students felt more enthusiastic, confident, and independent, as learning became accessible anytime and anywhere. Teachers benefited from easier material design, student monitoring, and feedback, though some faced challenges with technology mastery, limited internet, and device access. Training and support helped address these barriers. Overall, Schoology-based materials improved motivation, participation, critical thinking, and collaboration, supporting 21st-century education needs. The study emphasizes the importance of digital integration and broad support from schools, teachers, parents, and government.